Improving biomethane yield by strengthening acidification of maize stover in two-phase anaerobic digestion - Tong, Huan; Zhou, Baoyu; Liu, Chunmei; Wachemo, Akiber Chufo; Li, Xiujin; Zuo, Xiaoyu (International Journal of Agricultural and Biological Engineering, 2020)
In this study, the acidification and two-phase anaerobic digestion (AD) were conducted in batch and continuous stirred tank reactors, respectively, to determine the effect of acidification on methane production in AD. The results showed that two-phase AD achieved an observable enhancement in the methane production under optimal acidification conditions (organic loading rate of 60 g TS/L, the ratio of raw material to inoculum (based on dry weight) of 2:1, the temperature of 45°C, urea concentration of 4%, and time of 6 d). Under these conditions, the daily biogas and biomethane productions were 0.48 L/g TS and 0.30 L/g TS, respectively, which were 26.32% and 57.89% higher than those of the untreated group, respectively. The ammonia nitrogen (AN), alkalinity, and pH value of the methanogenic phase of C4 continued to increase up to 956 mg/L, 5680 mg/L, and 7.41, respectively, after 60 d, which might have destroyed the stability of the system. Therefore, for the purpose of reusing the nitrogen source, reducing AN, and maintaining the stability of the reaction system, another set of acidification and two-phase AD with water pretreatment using the discharge of the methanogenic phase of C4 as the inoculum was subsequently conducted. The results showed that the daily biogas productions of single-phase and two-phase AD were 5.26% and 15.79% higher than that of the untreated group, respectively; similarly, their daily methane yields were 10.42% and 21.05% higher than that of the untreated group.Keywords: alkaline pretreatment, two-phase anaerobic digestion, strengthening acidification, maize stover, reactor, biogas, biomethane productionDOI: 10.25165/j.ijabe.20201304.4654Citation: Tong H, Zhou B Y, Liu C M, Wachemo A C, Li X J, Zuo X Y. Improving biomethane yield by strengthening acidification of maize stover in two-phase anaerobic digestion. Int J Agric & Biol Eng, 2020; 13(4): 226–231.